Optimalisasi Pengguna Memori Virtual Pada Sistem Operasi Windows 10 - Apriana, Shalwa Putri; Hidayat, Rahmat; Rivani, Elkin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Virtual memory plays an essential role in contemporary operating systems like Windows 10, particularly in accommodating big data applications that need significant memory resources. This study seeks to evaluate how virtual memory optimization affects system performance using experimental techniques. Evaluations were performed utilizing benchmark software like Cinebench R20 and Unigine Heaven to assess the performance of the GPU and CPU. With virtual memory activated, the findings indicate a rise in data processing by 5-10% and a notable decrease in application response time. These findings hold significant consequences for application developers and users of systems with limited resources, since virtual memory can enhance physical memory capacity and improve overall system performance.